The evolving landscape of pulmonary arterial hypertension clinical trials. Issue 10366 (26th November 2022) - Weatherald, Jason; Boucly, Athénaïs; Peters, Anthony; Montani, David; Prasad, Krishna; Psotka, Mitchell A; Zannad, Faiez; Gomberg-Maitland, Mardi; McLaughlin, Vallerie; Simonneau, Gérald; Humbert, Marc; ,
Summary: Although it is a rare disease, the number of available therapeutic options for treating pulmonary arterial hypertension has increased since the late 1990s, with multiple drugs developed that are shown to be effective in phase 3 randomised controlled trials. Despite considerable advancements in pulmonary arterial hypertension treatment, prognosis remains poor. Existing therapies target pulmonary endothelial dysfunction with vasodilation and anti-proliferative effects. Novel therapies that target proliferative vascular remodelling and affect important outcomes are urgently needed. There is need for additional innovations in clinical trial design so that all emerging candidate therapies can be rigorously studied. Pulmonary arterial hypertension trial design has shifted from short-term submaximal exercise capacity as a primary endpoint, to larger clinical event-driven trial outcomes. Event-driven pulmonary arterial hypertension trials could face feasibility and efficiency issues in the future because increasing sample sizes and longer follow-up durations are needed, which would be problematic in such a rare disease. Enrichment strategies, innovative and alternative trial designs, and novel trial endpoints are potential solutions that could improve the efficiency of future pulmonary arterial hypertension trials while maintaining robustness and clinically meaningful evidence.